THE INFLUENCE OF LEADERSHIP, ORGANIZATIONAL CULTURE, MOTIVATION AND COMPENSATION ON EMPLOYEE PERFORMANCE IN REGIONAL APPARATUS ORGANIZATIONS (OPD) AT BAPERLITBANG KARIMUN REGENCY - Sumiyati Sumiyati; Bambang Satriawan; Chablullah Wibisono; Ngaliman Ngaliman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This research aims to analyze the influence of motivation, compensation, and commitment in an organization towards the Teacher’s Performance in Tunas Karya Pangkalpinang Foundation. In this research, the population is 50, with 35 respondents taken as a sample with purposive sampling method. The research population ranges from varied education background (from Associates Degree to Masters Degree), employee’s age ranging from 25 years to above, and minimal 5 years of duty with the rank/category ranges from 2nd grade (golongan II). The measurement is done with likert scale resulting to 7 alternatives of answer. The instrument tests done in this research are validity and reliability test, whereas the model test done in this research is co-efficiency determination, F test (Goodness of Fit) and t-test. Hypothesis test used in this research is done with regression analysis with the t-count. The hypothesis assessment uses t count for the frequency distribution towards significance rate (α) 5%. The result of the research shows that the variable of motivation, compensation, and commitment of organization works simultaneously to influence the teacher’s performance in Tunas Karya Pangkalpinang Foundation. However, with the t-test, not all Sig t results below 0,05. Based on the research result, there are some conclusions taken which are: (1) The motivation provides significant and positive influence towards the teacher’s performance in Tunas Karya Pangkalpinang Foundation. (2) The compensation does not provide significant and positive influence towards the teacher’s performance in Tunas Karya Pangkalpinang Foundation. (3) Organizational commitment provides significant and positive influence towards the teacher’s performance in Tunas Karya Pangkalpinang Foundation.